Organic micropollutants on river sediments from Rio de Janeiro State, Southeast Brazil - Torres João Paulo Machado; Malm Olaf; Vieira Elisa Diniz Reis; Japenga Jan; Koopmans Gerwin Ferdinand (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2002)
The paper is a contribution for the knowledge upon concentrations and fate of different kinds of organic micropollutants in Tropical River system from a very industrialized region in Brazil. The presented data was obtained during three years of an International Research Project between Brazilian and Dutch institutions. The sediments were sampled at the Paraiba do Sul-Guandu river watershed, the most important watercourse of Rio de Janeiro state, where up 90 % of the population depends on its water for domestic uses. After extraction with non-polar solvents in a hot sohxlet device and clean up using chromatographic columns, three classes of organic micropollutants were analyzed: organochlorine insecticides (OCs), polychlorinated biphenyls (PCBs) and polynuclear aromatic hydrocarbons (PAHs). The organochlorines, including the PCBs were scarcely present in the collected samples probably reflecting the restrictions of use of this class of compounds in the Brazilian market. However, the PAHs levels were high at the vicinity of a huge steelworks located in the city of Volta Redonda. This contamination is probably due to the massive use of coal in the above-cited metallurgical plant.